Acceptability and feasibility of collecting psychosocial data from fathers of very low birth weight infants. (September 2017) - Bagge, SR; Westgate, B; Few, K; Clarke, P; Adlam, A; Walsh, J; O'Brien, M
The aim of this study was to determine the feasibility and acceptability of collecting outcome data from parents of very low birth weight (VLBW) infants and to explore the psychological and social adaptation of fathers. Questionnaires were distributed to 38 parents of VLBW infants and 36 parents of term infants within a hospital Neonatal Intensive Care Unit. Field notes were also taken. Parents indicated collecting outcome data in this population was feasible and acceptable, but barriers and difficulties in data collection were identified, particularly for fathers. Furthermore, parents highlighted a lack of emotional support for fathers. In conclusion, research with parents of VLBW infants should happen with consultation, flexibility and measures designed specifically for this population.